Prime Toeic reading : (Tổng hợp, 2014)
The Toeic test is an important test. More than two million people take this test every year. Today, it is important for people all over the word to use English, and the Toeic test is one of the ways to measure the English ability of non-native speakers. In addition, a high score on this test can help them get a good job or a promotion.